2010
DOI: 10.1016/j.biopsych.2009.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Chromatin Modification Facilitates Extinction of Cocaine-Induced Conditioned Place Preference

Abstract: Background: Recent evidence suggests that epigenetic mechanisms have an important role in the development of addictive behavior. However, little is known about the role of epigenetic mechanisms in the extinction of drug-induced behavioral changes. In this study we examined the ability of histone deacetylase (HDAC) inhibitors to facilitate extinction and attenuate reinstatement of cocaine-induced conditioned place preference (CPP). Methods: C57BL/6 mice were subject to cocaine-induced CPP using 20mg/kg dose. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
140
2
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(160 citation statements)
references
References 42 publications
14
140
2
2
Order By: Relevance
“…Our findings showing the NaBu treatment reduced both cocaine-seeking and Bdnf exon IV expression are consistent with other reports showing beneficial effects of HDAC inhibition in reducing cocaine-seeking and extinction of conditioned place preference for cocaine (Malvaez et al 2010;2013). Although NaBu is a non-specific HDAC inhibitor, and in this study its effects were examined following systemic administration, evidence suggests that inhibition of HDAC activity affects the expression of only approximately 2% of genes (Van Lint et al 1996;Davie et al 2003).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings showing the NaBu treatment reduced both cocaine-seeking and Bdnf exon IV expression are consistent with other reports showing beneficial effects of HDAC inhibition in reducing cocaine-seeking and extinction of conditioned place preference for cocaine (Malvaez et al 2010;2013). Although NaBu is a non-specific HDAC inhibitor, and in this study its effects were examined following systemic administration, evidence suggests that inhibition of HDAC activity affects the expression of only approximately 2% of genes (Van Lint et al 1996;Davie et al 2003).…”
Section: Discussionsupporting
confidence: 92%
“…In support of this possibility we also demonstrated that treatment of sodium butyrate, a HDAC inhibitor that, like exercise, modulates gene transcription, including Bdnf exon IV expression, provided beginning during early abstinence mimicked both the behavioral and molecular effects of wheel running. This finding is consistent with other reports showing beneficial effects of HDAC inhibition in reducing cocaine-seeking and extinction of conditioned place preference for cocaine (Malvaez et al 2010;2013) and further suggests epigenetic modification of chromatin containing the Bdnf gene during early abstinence as a possible mechanism.…”
Section: Role Of Bdnf Mediating the Efficacy Of Exercisesupporting
confidence: 93%
See 1 more Smart Citation
“…Tissue preparation and immunohistochemical analysis was performed as described previously (Vecsey et al, 2007;Malvaez et al, 2010). Briefly, coronal sections of paraformaldehyde-fixed, cryoprotected brains were cut with a cryostat at a thickness of 20 mm at the level of the hippocampus and collected in PBS.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Chez les rongeurs, cette approche suggère que le développement des comportements liés à l'addiction était sans doute relié à des modifications épigénétiques, même si les résultats ne sont pas toujours concordants. C'est ainsi que des inhibiteurs non sélectifs des HDAC : (1) réduisent la consommation de cocaïne pendant la phase d'acquisition de l'autoadministration, ainsi que la motivation des rats à s'autoadministrer la drogue [42] ; (2) réduisent la consommation d'éthanol par des souris et la motivation des rats à s'administrer de l'éthanol [43] ; (3) facilitent l'extinction de la préférence de place induite par la cocaïne [44] ; (4) réduisent la préférence de place induite par la nicotine, mais pas l'aversion de place provoquée par des doses plus élevées [45] ; (5) inhibent la sensibilisation comportementale provoquée par l'éthanol [46] ; et (6) réduisent le comportement de recherche de cocaïne après une période de sevrage de trois semaines (rechute) [47]. D'autre part, un traitement similaire avec souvent les mêmes Les HDAC sistent pendant une bonne partie de la vie, sous-tendraient la trace d'évènements traumatisants se produisant durant les tout premiers jours de vie.…”
Section: Effets Comportementaux Des Inhibiteurs Des Hdacunclassified